Oscillatory integration windows in neurons - Nitin Gupta (Nature Portfolio, 2016)
Neural oscillations have been proposed to process information by generating cyclic integration windows: specific portions of the oscillatory cycle when a post-synaptic neuron is especially sensitive to coincident inputs. Here, the authors demonstrate the existence and mechanism of integration windows in Kenyon cells in the locust olfactory system.